Między- i metazmysły – percepcja w dobie sztuki multimedialnej - Mądro, Andrzej (Res Facta Nova, 2018)
The mechanism of perceiving the world by mankind is still an unfathomable, yet highly discussed, problem of modern science in its various fields. If the issue is considered in the specific context of contemporary music and art – electroacoustic, multimedia, interactive – questions arise: how do the hearing and the mind react to the new synthesized sounds? What are the mechanisms and rules of multi-sensory perception? Are new perceptual skills developing in the face of new aesthetic situations? Does mankind in the age of the new media take another step on the long path of its “sensory evolution”?New media art often puts the senses to the proof; it is a game played with perception, with its limitations and capabilities. In turn, intensification of experience appears to the audience as liberation, escapism, but also as a search for new ways of knowing.